Statutes and Regulations of the Polish Pontifical College in Rome in 2002 - STĘPIEŃ, MAREK (Prawo Kanoniczne, 2013)
The Polish Pontifical College in Rome is an institution of the church, which remains particularly dependent on the Holy See and at the same time, is subject to the authority and supervision of the Polish Episcopal Conference.Polish priests are admitted to the College after the completion of their studies and spiritual formation at the seminary. They are then directed by their bishop to pursue specialized studies at Roman ecclesiastical universities. The Polish Pontifical College is an institution with legal personality, under Canon Law. This legal personality is also recognized within the Italian legal system by the Italian Republic. The College’s rector is the legal representative. The Statutes and the Rules of the College emphasize the importance of spiritual and intellectual formation of student priests. The 1991, Principles of Life and Rules of the Papal Seminary Lombardo, Saint Ambrosio and St. Charles of Rome were used in developing the new Statutes and the Rules of the Polish Pontifical College.